2017
DOI: 10.22146/jpsi.17378
|View full text |Cite
|
Sign up to set email alerts
|

Meningkatkan Kematangan Karier Peserta Didik SMA dengan Pelatihan Reach Your Dreams dan Konseling Karier

Abstract: Abstract. Career maturity is a condition that needed to choice the program in higher level study. Henceforth, the low level of career maturity in senior high school student has to be solved with the comprehensive intervention as soon as possible. The purpose of this research is to know the effectivity of Reach Your Dreams Training and career counseling for improving career maturity in senior high school student. This research used Solomon Six Group Design. Subjects of this research are 42 senior high school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 3 publications
(3 reference statements)
3
6
0
9
Order By: Relevance
“…Another factor that creates low career maturity of students is that most of the students with special needs do not know planning and job that they have to choose after graduates, they have difficulty making decisions and are not sure about their careers, causing their careers to be immature. This statement is in line with previous research showing that adolescent students have a low level of career maturity (Lau et al, 2019;Saifuddin et al, 2017). Moreover, previous research showed that in the industrial world, children with special needs are more likely to be unemployed, experiencing discrimination, being unemployed more often, and getting lower wages (Dispenza, 2019;Lombardi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Another factor that creates low career maturity of students is that most of the students with special needs do not know planning and job that they have to choose after graduates, they have difficulty making decisions and are not sure about their careers, causing their careers to be immature. This statement is in line with previous research showing that adolescent students have a low level of career maturity (Lau et al, 2019;Saifuddin et al, 2017). Moreover, previous research showed that in the industrial world, children with special needs are more likely to be unemployed, experiencing discrimination, being unemployed more often, and getting lower wages (Dispenza, 2019;Lombardi et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Menurut hasil survei, 91% perusahaan percaya bahwa lulusan perguruan tinggi belum siap untuk langsung bekerja [2], [4]. Faktor lain yang melatarbelakangi tingginya angka pengangguran adalah kurangnya perencanaan karir bagi lulusan perguruan tinggi [5].…”
Section: Pendahuluanunclassified
“…Penelitian pengembangan panduan portofolio karier ini juga mendukung penelitian sebelumnya yang juga berkaitan dengan penelitian sebelumnya antara lain Career Counseling Program to Improve Maturity Student of SMK, (Saifuddin, Ruhaena, & Pratisti, 2017) dimana penelitian ini menunjukkan (1) kematangan karier siswa secara umum di SMK N 11 Bandung berkategori sedang, (2) indikator yang memiliki persentase terbesar adalah keterlibatan, independensi, dan pemilihan pekerjaan, sementara indikator terendah adalah kompromi, pemahaman diri, dan pengetahuan pekerjaan, (3) program bimbingan karier efektif untuk meningkatkan kematangan karier siswa. Dalam sebuah artikel penelitian yang berjudul Profesional Development Through Teaching Portofolio dalam (Wijayanti, 2008) juga menjabarkan tentang efektifvas mengajar melalui portofolio yakni bahwa guru sebagai profesional harus menyadari pentingnya profesi.…”
Section: Pembahasanunclassified